Disribution kinetics of cardioprotector ALM-802 in rat organs and tissues - O. Yu. Kravtsova; G. B. Kolyvanov; A. A. Litvin; P. O. Bochkov; V. P. Zherdev (LLC "Publisher OKI", 2022)
The distribution kinetics of a compound with cardioprotective activity, N1-(2,3,4-trimethoxybenzyl)-N2-{2-[(2,3,4-trimethoxybenzyl)amino] ethyl}-1,2-ethanediamine (ALM-802) in rat tissues and organs after single intragastric administration at a dose of 100 mg/kg. The values of ALM-802 tissue availability were determined. Tissue availability of ALM-802 falls in a row: kidneys→liver→heart→spleen→skeletal muscle→brain (129.3; 27.2; 20.9; 15.3; 5.9 and 0.3, respectively). It was found that ALM-802 is excreted from the body rather slowly: kel values ranged from 0.0252 to 0.0885 h-1, MRT values were 7.6-59.3 h.